Public Health Policy in Donggala Regency - Pasinringi, Andi; Samad, Muhammad Ahsan; Alamsyah, Muh. Nur; Jeni, (Technium Social Sciences Journal, 2020)
This study aims to determine how the implementation of Village Fund policies in addressing the problems of community health development in Donggala Regency, Central Sulawesi Province. The technique for determining informants in this area was carried out after determining the sample area by referring to the Village Minister Regulation (Permendesa) Number 2 of 2016 concerning the Developing Village Index (IDM), which maps Villages into the Village category. Donggala Regency has three categories of villages, namely: very disadvantaged villages, underdeveloped villages, and developing villages. And for each Village Category, informants were determined purposively, as was the technique of determining informants at the Health Office and the Community Development and Village Government (DPMD) Office, informants were determined purposively. The results of the study concluded that the implementation of public health development policies in Donggala Regency was not well realized, however, in this study it was found that the Van Meter & Van Horn policy implementation model was very appropriate to be used in assessing the performance of complex policies.